What evidence exists for the effectiveness of on‑farm conservation land management strategies for preserving ecosystem services in developing countries? A systematic map - Thorn, J.P.R.; Friedman R; Benz D; Willis, K.J.; Petrokofsky, G. (Springer, 2016)
Background: An extensive body of evidence in the field of agro-ecology claims to show the positive effects that maintenance of ecosystem services can have on meeting future food demand by making farms more sustainable, productive and resilient, which then contributes to improved nutrition and livelihoods of farmers. However, inconsistent effects have commonly been reported, while empirical evidence to support assumed improvements is largely lacking. Overall, a coherent synthesis and review of the evidence of these claims is largely absent from the literature.